Teaching English using social media: Pre-service English teachers’ perceptions - Ahmad Jailani; Kurniati; Ervina (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Social media has been widely used in many aspects of life, including education. Many teachers nowadays have made use of social media. This study aims to explore the perceptions of pre-service English teachers on the use of social media in teaching English. This study was a survey research with a quantitative and qualitative approach. The data were collected through an interview questionnaire via Google form from 39 pre-service English teachers now studying at STAIN Bengkalis. The result showed that pre-service English teachers have positive perceptions on the use of social media in teaching English. It can be seen from the finding that 38 out of 39 respondents would like to use social media when they become teachers in the future. In their perception, WhatsApp, YouTube, Instagram, and Facebook are the most useful social media to be used in teaching English. Incorporating social media into education have some benefits, such as: encompassing enhanced comprehension, greater student self-sufficiency, boosted enthusiasm, efficiency in terms of costs, and the promotion of innovation among teachers. Nevertheless, it is important to recognize the hurdles associated with ensuring dependable internet access, fostering digital literacy, fostering creativity when designing lessons, and effectively managing how students utilize these resources. Findings from this study strengthen the fact that social media must be used in teaching and learning process and urge faculty to preparing future teachers with satisfied ability to use information technology or social media in teaching.